Hyperprogressive disease in patients suffering from solid malignancies treated by immune checkpoint inhibitors: A systematic review and meta-analysis - Zhao, Zijun; Bian, Jin; Zhang, Junwei; Zhang, Ting; Lu, Xin (Frontiers in Oncology, 2022)
Introduction Hyperprogressive disease (HPD) is a paradoxically rapid disease progression during or shortly after anti-tumor treatment, especially immune checkpoint inhibitors (ICIs). Various diagnosis criteria of HPD caused heterogeneous incidence rates in different clinical research and no consensus on potential risk factors associated with HPD occurrence. Hence, we aimed to summarize incidence of HPD in ICIs treatment for solid tumors. Clinicopathological factors associated with HPD were also analyzed. Methods Clinical studies about HPD during/after ICIs treatment of solid malignancies were included. Pubmed, Embase and Cochrane library were searched for eligible studies published before October 7. Newcastle-Ottawa Scale was used to assess quality of included studies. Random-effect and fix effect models were respectively used for pooling incidence of HPD and analysis of risk factors of HPD. Heterogeneity, subgroup analysis and publication bias were also analyzed. All meta-analysis was performed via R software (v4.0.2). Results 41 studies with 6009 patients were included. The pooled incidence of HPD was 13.2% (95% CI, 11.2%-15.4%). Head and neck cancer (HNC) had the highest incidence of HPD (18.06%) and melanoma got the lowest one (9.9%). Tumor types (P=0.0248) and gender ratio (P=0.0116) are sources of heterogeneity of pool incidence of HPD. For five clinicopathological factors associated with HPD, only programmed cell death protein 1 ligand 1 (PD-L1) positivity was a preventive factor (odds ratio= 0.61, P<0.05). High lactate dehydrogenase (LDH) level (OR=1.51, P=0.01), metastatic sites >2 (OR=2.38, P< 0.0001), Eastern Cooperative Oncology Group Performance Score ≥2 (OR=1.47, P=0.02) and liver metastasis (OR= 3.06, P< 0.0001) indicated higher risk of HPD. Conclusions The pooled incidence of HPD was less than 15% and HNC had the highest incidence of HPD. LDH and PD-L1 would be remarkable biomarker for prediction of HPD in future medical practice. Keywords Hyperprogressive disease, solid malignancy, immune checkpoint inhibitor, incidence and prognosis, systematic review and meta-analysis